2017
DOI: 10.1016/j.system.2017.09.002
|View full text |Cite
|
Sign up to set email alerts
|

Multimodal instruction-giving practices in webconferencing-supported language teaching

Abstract: Supplementary material: doi.org/10.1016/j.system.2017.09.002International audienceThis paper focuses on instruction-giving practices, a crucial but under-researched aspect of online language tutorials. The context for this qualitative study is a telecollaborative exchange focussing on French as a foreign language. We investigate trainee teachers' instructions for a role-play rehearsal task during webconferencing-supported language teaching sessions. Multimodal (inter)action analysis (Jewitt, Bezemer, & O'Hallo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 21 publications
0
17
0
Order By: Relevance
“…Shi, Stickler, & Lloyd, 2017) would also help better understand participants' attention and awareness. Concerning participant numbers, we incorporated two learners to allow for comparisons with previous research (Satar & Wigham, 2017), yet individual classes are perhaps more common in online teaching. To overcome this potential limitation, we have collected further data where the same task is conducted with one learner to explore whether the use of the print mode would differ in this context.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Shi, Stickler, & Lloyd, 2017) would also help better understand participants' attention and awareness. Concerning participant numbers, we incorporated two learners to allow for comparisons with previous research (Satar & Wigham, 2017), yet individual classes are perhaps more common in online teaching. To overcome this potential limitation, we have collected further data where the same task is conducted with one learner to explore whether the use of the print mode would differ in this context.…”
Section: Discussionmentioning
confidence: 99%
“…Comparing written instructions in an asynchronous teaching platform with verbal instructions in multimodal synchronous teaching, Cappellini and Combe (2017) reported that trainee-teachers experienced unexpected challenges concerning managing the digital task resources, such as having to instruct the learners on how to download a document, especially in the synchronous platform. Satar & Wigham (2017) addressed the multimodal resources trainee-teachers employed whilst delivering task instructions, and demonstrated the use of textchat in introducing key vocabulary items in both spoken and written language (dual modality).…”
Section: Delivering Task Instructionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hampel and Stickler 2012;Guichon and Cohen 2014). These and other studies have explored videoconferencing practices both in interaction between dispersed individuals (Satar 2013;Guichon and Cohen 2014;Rusk and Pörn 2019) and between small groups or larger classroom cohorts (Austin, Hampel, and Kukulska-Hulme 2017;Satar and Wigham 2017).…”
Section: Coordinating Joint Attention In the Materials Ecology Of Video-mediated Instructional Interactionmentioning
confidence: 99%
“…Mobile instant messaging helps learners to exchange immediate feedback on their language use [46]. Blackboard Collaborate Ultra, which is a synchronous video/screencast recording system, provides space for learners to interact with peers and teachers during online classes in real time [47,48].…”
Section: Computer-mediated Interactionsmentioning
confidence: 99%